Water uptake by fresh Indonesian peat burning particles is limited by water-soluble organic matter - Chen, Jing (2018)
The relationship between hygroscopic properties and chemical characteristics of Indonesian biomass burning (BB) particles, which are dominantly generated from peatland fires, was investigated using a humidified tandem differential mobility analyzer. In addition to peat, acacia (a popular species at plantation) and fern (a pioneering species after disturbance by fire) were used for experiments. Fresh Indonesian peat burning particles are almost non-hygroscopic (mean hygroscopicity parameter, κ<0.06) due to predominant contribution of water-insoluble organics. The range of κ spans from 0.02 to 0.04 (dry diameter=100nm, hereinafter) for Riau peat burning particles, while that for Central Kalimantan ranges from 0.05 to 0.06. Fern combustion particles are more hygroscopic (κ=0. 08), whereas the acacia burning particles have a mediate κ value (0.04). These results suggest that κ is significantly dependent on biomass types. This variance in κ is partially determined by fractions of water-soluble organic carbon (WSOC), as demonstrated by a correlation analysis (R=0.65). κ of water-soluble organic matter is also quantified, incorporating the 1-octanol–water partitioning method. κ values for the water extracts are high, especially for peat burning particles (A0 (a whole part of the water-soluble fraction): κ=0.18, A1 (highly water-soluble fraction): κ = 0.30). This result stresses the importance of both the WSOC fraction and κ of the water-soluble fraction in determining the hygroscopicity of organic aerosol particles. Values of κ correlate positively (R=0.89) with the fraction of m∕z 44 ion signal quantified using a mass spectrometric technique, demonstrating the importance of highly oxygenated organic compounds to the water uptake by Indonesian BB particles. These results provide an experimentally validated reference for hygroscopicity of organics-dominated particles, thus contributing to more accurate estimation of environmental and climatic impacts driven by Indonesian BB particles on both regional and global scales.